Deployment of Lean Six Sigma DMAIC methodology to improve productivity of a can manufacturing industry - Shamsuzzaman, Mohammad; AlHerimi, Nadin; Haridy, Salah; Shamsuzzoha, Ahm; Abumadi, Farah; Jabban, Rasha Al; Rami, Haya; Asem, Joumana (Inderscience, 2023)
This study proposes and follows a specific and systematic define-measure-analyse-improve-control (DMAIC)-based Lean Six Sigma (LSS) implementation framework for improving the productivity of a can manufacturing industry. A case study research methodology is adopted and implemented through the proposed LSS framework. The effectiveness of the LSS framework is evaluated in a metal fabrication industry producing metallic cans. It is found that the implementation of the LSS project improves the annual productivity of the company by about 511,992 non-defective products, which can successfully lead to an increase in the annual sales of about $25,600. This improvement is expected to maintain an efficient production process, increase customer satisfaction, and enhance company's goodwill and profit. This study is expected to help improving the understanding of how LSS methodology can be implemented in solving quality related problems and offer valuable insights for practitioners in metal can manufacturing industries.
Keywords: Productivity improvement; Lean Six Sigma; DMAIC; Define-Measure-Analyze-Improve-Control; Metal can industry; Pareto chart; Control chart; Cause and effect diagram; 5-why analysis; Simulation; fi=Tuotantotalous|en=Industrial Management|